An anti-collision algorithm for RFID-based robots based on dynamic grouping binary trees. (October 2017) - Zhang, Yin; Yang, Fan; Wang, Qian; He, Qianlin; Li, JiaCheng; Yang, Yue
Graphical abstract: Abstract: This paper investigates the conventional algorithms for addressing the issue of tag collision in radio-frequency identification (RFID) systems. To improve the efficiency of RFID reader inquiry, this paper proposes an approach based on dynamic grouping binary trees, named DGBT, for RFID-based robots. Through DGBT, the collision probability and query times of RFID readers are lowered by adaptive anti-collision prefixes, the efficiency of RFID identification is improved via the group-based approach, and the binary-tree-based queries within groups are ensured to be stable, flexible, effective and practicable. Analysis and simulation verify that the query times and throughput rate are significantly improved by DGBT.